Answer: (
![-(1)/(3),-(13)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/prlduven8aqi66wwdh6orfv38rl955i73a.png)
Explanation:
Substitut (x-4) into the equation of 4x-y=3
(Substitute what y equals into the equation
Make sure to keep parentheses!
That becomes 4x-(x-4)=3
Than you must distribute the negative to x and to -4
When you do it creates the equation of 4x-x+4=3
When combining like terms you get: 3x+4=3
Then solve -4 -4
3x=-1
3 3 x=-1
3
Than substitute the x in for the equation of y=x-4 to find what y equals! since you know that x equals -1/3 than subtract -1/3 - 4 to get
y= -13
3